Novel and distinct operational principles of intralaminar thalamic neurons and their striatal projections. - Lacey, C; Bolam, J; Magill, P (2007)
Neurons of the intralaminar thalamus, including central lateral (CL) and parafascicular (Pf) nuclei, innervate the cortex and striatum and are important for cognitive, sensory, and motor processes. We tested the hypothesis that CL and Pf neurons provide functionally distinct inputs to the striatum. We performed recordings of single CL and Pf neurons in anesthetized rats and, after juxtacellularly labeling the neurons, their somatodendritic features and synaptic connections were characterized. All CL neurons (n = 31) discharged classic low-threshold Ca2+ spike bursts during cortical slow-wave activity in vivo. In contrast, Pf neurons (n = 52) rarely fired such bursts, but instead discharged groups of spikes at relatively low frequencies. The activity of CL and Pf neurons was often temporally coupled to cortical slow oscillations. Identified CL neurons possessed archetypal "bushy" dendrites and preferentially established synapses with dendritic spines (91% of synapses) of striatal projection neurons. Pf neurons possessed "reticular-like" dendrites, and, on average, preferentially established synapses with dendritic shafts (63%) in striatum, although connectivity was markedly heterogeneous across neurons. Two of the six Pf neurons studied exclusively targeted dendritic shafts, whereas another neuron almost exclusively (97%) targeted spines. The remaining three neurons preferentially targeted dendritic shafts (53-70%). Thus, the fundamental properties of CL and Pf neurons differ (the latter do not express the typical operational principles of thalamic relay neurons), and they provide different temporally patterned inputs to distinct striatal targets. This mechanistic diversity likely underpins the transmission of specific and discrete information from intralaminar thalamic nuclei to striatal and cortical targets.